Effect of roof materials and weather patterns on the quality of harvested rainwater in Shanghai, China. (10th January 2021) - Mao, Jian; Xia, Boyu; Zhou, Yun; Bi, Fan; Zhang, Xiaodong; Zhang, Wei; Xia, Siqing
Abstract: As the supplementary of domestic water and even as potable water, roof harvested rainwater seems increasingly probable worldwide due to the shortage of fresh water resource. In this study, we compared the quality of harvested rainwater under different meteorological conditions and roofing materials (i.e., galvanized metal, ceramic tile, concrete and asphalt). Results showed that the quality of roof harvested rainwater in the rainwater tank was superior to the first-flush tank, but reusing directly without diversion was not recommended. Compared with other three roof types, ceramic tile was ideally qualified for roof rainwater harvesting, which achieved the highest quality of recycled rainwater (e.g., turbidity (5.03 ± 1.73 NTU), TOC < 22.86 mg·L −1, TN < 4.23 mg·L −1, NH4 + -N < 1.85 mg·L −1, NO3 − -N < 1.56 mg·L −1, Al < 0.01 mg·L −1, Fe < 0.02 mg·L −1, Zn (No detection), Pb (No detection)). However, asphalt was the last choice as roof material to harvest rainwater due to the worst recycled water quality. Additionally, weather patterns and features could have significant influence on the water quality parameters, and rainfall was the principal meteorological factor. Moreover, antecedent dry days had a great interaction with the quality of rainwater in first-flush tank for asphalt roof. This study lays the foundation for roof rainwater harvesting by selecting suitable roof materials under various weather patterns. Based on the results of the economic analysis, investing roof rainwater harvested system with large catchment area may have low risk and can quickly recover costs in the life cycle. Graphical abstract: Image 1 Highlights: Harvested rainwater quality at various roof materials and weather patterns has been investigated. The quality of roof harvested rainwater in the rainwater tank was superior to the first-flush tank. Ceramic tile was ideally qualified to achieve the highest recycled rainwater quality. Rainfall was the principal meteorological factor to affect water quality parameters. Antecedent dry days had a great interaction with the quality of rainwater in first-flush tank.